2023
DOI: 10.3390/ph16111543
|View full text |Cite
|
Sign up to set email alerts
|

Lutein/Zeaxanthin Isomers and Quercetagetin Combination Safeguards the Retina from Photo-Oxidative Damage by Modulating Neuroplasticity Markers and the Nrf2 Pathway

Emre Sahin,
Cemal Orhan,
Nurhan Sahin
et al.

Abstract: Exposure to light-emitting diode (LED) light is a primary cause of retinal damage, resulting in vision loss. Several plant-derived substances, such as lutein and quercetagetin (QCG), show promise in supporting eye health. In this study, the impact of lutein/zeaxanthin (L/Z, Lutemax 2020) and QCG were evaluated individually and together in a rat model of LED-induced retinal damage. A total of 63 Wistar rats were allocated into nine groups (n = 7). For 28 days, the rats received L/Z (10 or 20 mg/kg BW), querceti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Overall, previous studies have demonstrated that lutein interacts directly with Nrf2 [ 53 ], resulting in the increased expressions of several antioxidant and cytoprotective proteins such as HO-1 and Cx-43 [ [54] , [55] , [56] ]. Specifically, it is known that the activation of Nrf2 is triggered by the interaction of lutein with nuclear receptors, which then binds to ARE/EpRE sequence in HO-1 and Cx-43 genes, notably increasing their expressions [57].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, previous studies have demonstrated that lutein interacts directly with Nrf2 [ 53 ], resulting in the increased expressions of several antioxidant and cytoprotective proteins such as HO-1 and Cx-43 [ [54] , [55] , [56] ]. Specifically, it is known that the activation of Nrf2 is triggered by the interaction of lutein with nuclear receptors, which then binds to ARE/EpRE sequence in HO-1 and Cx-43 genes, notably increasing their expressions [57].…”
Section: Discussionmentioning
confidence: 99%